2015
DOI: 10.7883/yoken.jjid.2014.405
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Investigation of Hantavirus Infection in Patients with Previous Thrombocytopenia, and Elevated Urea and Creatinine Levels in an Epidemic Region of Turkey

Abstract: SUMMARY:The first cases of Hantavirus infection in Turkey were reported in early 2009 in the Zonguldak and Bartin provinces. The aim of this study was to investigate the presence of Hantavirus antibodies in patients who had clinical and laboratory findings that were potentially associated with Hantavirus infection prior to the epidemic in Bartin in 2009. After screening 314,577 medical records from between 2007 and 2009, the clinical and laboratory data for 442 patients meeting the criteria of coexistent throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In the current outbreak, dealing with rodent control activities in gardens or in annexes of the house and being male were found to be significant risk factors for human hantavirus infection. In two seroprevalence studies—one performed at the outbreak area and the other at the Giresun Province situated at the Eastern part of the Black Sea Region—being male, the presence of a barn near one's house, living in the woods or an adobe house and working in a forest were found to be statistically significant risk factors for hantavirus infection (Gozalan et al, ; Sevencan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current outbreak, dealing with rodent control activities in gardens or in annexes of the house and being male were found to be significant risk factors for human hantavirus infection. In two seroprevalence studies—one performed at the outbreak area and the other at the Giresun Province situated at the Eastern part of the Black Sea Region—being male, the presence of a barn near one's house, living in the woods or an adobe house and working in a forest were found to be statistically significant risk factors for hantavirus infection (Gozalan et al, ; Sevencan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, orthohantavirus IgM levels were investigated instead to determine suspected acute cases among patients with FUO. Generally, this study showed that IgM‐positive patients were more females than males, but this was not statistically significant as given by the small case numbers (Latronico et al, ; Sevencan et al, ). We did not find a relationship with some risk factors such as living place, garden or fieldwork or the observation of rodents with IgM‐positive cases (Botros et al, ).…”
Section: Discussionmentioning
confidence: 60%
“…In our study, the high rate of positive IgG antibodies by ELISA shown here could be false‐positive, originating from the sensitivity of the screening test. Moreover, the difference between ELISA and confirmatory assays has been shown in several orthohantavirus seroprevalence studies (Engler et al, ; Sevancan et al, ). The different results by immunoblotting and IIFT can be explained by sensitivity (immunoblotting—96.1%, IIFT—99%) and specificity (immunoblotting—100%, IIFT—98%) of the used assays (mikrogen.de, euroimmun.de).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, many sero-epidemiological investigations of viruses of public health importance, i.e., DENV, CCHFV, Rift Valley fever virus, WNV, Usutu virus, CHIKV, Bourbon virus, Hantavirus, ZIKV, and SARS-CoV-2, have been carried out to confirm the presence of virus-specific IgM and IgG antibodies, and subsequently, case confirmation using gold standard PRNTs or by virus isolation [74][75][76][77][78][79][80][81][82][83][84]. Due to cross-reactivity amongst the arboviruses, cell culture-based NTs are the preferred serological tool for case confirmation.…”
Section: Sero-epidemiological Investigations Vaccine Trials and Cross...mentioning
confidence: 99%